Potent antimicrobial activity of bone cement encapsulating silver nanoparticles capped with oleic acid - Prokopovich, Polina (J Biomed Mater Res B Appl Biomater, 2015)
Bone cement is widely used in surgical treatments for the fixation for orthopaedic devices. Subsequently, 2–3% of patients undergoing these procedures develop infections that are both a major health risk for patients and a cost for the health service providers; this is also aggravated by the fact that antibiotics are losing efficacy because of the rising resistance of microorganisms to these substances. In this study, oleic acid capped silver nanoparticles (NP) were encapsulated into Poly(methyl methacrylate) (PMMA)-based bone cement samples at various ratios. Antimicrobial activity against Methicillin Resistant Staphylococcus aureus, S. aureus, Staphylococcus epidermidis, Acinetobacter baumannii was exhibited at NP concentrations as low as 0.05% (w/w). Furthermore, the mechanical properties and cytotoxicity of the bone cement containing these NP were assessed to guarantee that such material is safe to be used in orthopaedic surgical practice. © 2014 The Authors. Journal of Biomedical Materials Research Part B: Applied Biomaterials Published by Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 273–281, 2015.